The Application of Lacan's Psychoanalytic Theory to the Character Development of Miki Sayaka and Sakura Kyouko in the Anime Madoka Magica (Cinematology: Journal Anthology of Film and Television Studies, 2024)
This study analyzes the deconstruction of the heroism myth in Puella Magi Madoka Magica through the lens of Lacanian psychoanalysis and Roland Barthes' Mythologies theory. The primary issue addressed in this research is how the series' narrative dismantles the traditional heroism myth commonly associated with the magical girl genre through the character arcs of Sayaka Miki and Kyouko Sakura. The research questions focus on how Lacan’s psychoanalytic stages are reflected in the development of Sayaka and Kyouko, as well as how the myth of heroism in the series is reproduced and deconstructed through Barthes' concept of modern mythology. The aim of this study is to reveal how Puella Magi Madoka Magica critiques the concept of heroism in popular culture and reconstructs existing myths to expose the exploitative system governing magical girls. This research employs a qualitative methodology with a narrative analysis approach, examining key episodes that represent the psychological transformations of the main characters. The findings indicate that Sayaka experiences the collapse of her idealism due to a confrontation with an unforgiving reality, whereas Kyouko undergoes a reconstruction of her worldview that ultimately contradicts her initial beliefs. The series not only deconstructs the heroism myth within the magical girl genre but also portrays how individuals struggle with the disparity between expectations and reality within an oppressive symbolic system.